Conservative management of vesicovaginal fistula: a rare case report - Shanmugham, Deepa; Kondra, Siritha; Vasudevan, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Vesicovaginal Fistula is a debilitating condition that has affected women for millinea. Spontaneous closures of VVF with continuous bladder drainage for varying periods have been reported by few authors. Here we present a case of post hysterectomy VVF managed conservatively. A 45 year old parous woman presented with continuous leakage of urine following hysterectomy. The clinical diagnosis of Vesicovaginal Fistula was proven by cystoscopy and CT cystography. VVF healed by continuous bladder drainage for 4 weeks. Non-surgical treatment with continuous bladder drainage can also result in complete healing of small VVFs.